PENGARUH LITERASI ASURANSI SYARIAH TERHADAP PERSEPSI MASYARAKAT DALAM MEMILIH ASURANSI SYARIAH JABODETABEK - Muhammad Rahmadion (2021)
This study aims to explain the effect of sharia insurance literacy on public perception in choosing sharia insurance. This study uses a quantitative approach. The sample in this study, namely JABODETABEK people who have an understanding of sharia insurance. To analyze the data, this study used the Likert scale method. This study also uses descriptive analysis methods and multiple linear regression and uses SPSS software as a tool to process data. The results of this study are sharia insurance literacy in the form of contracts in sharia insurance has a significant effect on public perception, sharia insurance literacy in the form of fund management in sharia insurance has significant effect on public perception and sharia insurance literacy in the form of surplus underwriting has no significant effect on public perception.